Evaluation of the efficacy of benzimidazole anthelmintics against different stages of gastrointestinal nematodes of young cattle - I. A. Arkhipov; A. I. Varlamova; A. V. Radionov (Российский паразитологический журнал, 2022)
The purpose of the research is to study the efficacy of benzimidazole anthelmintics against different development stages of gastrointestinal nematodes of young cattle.Materials and methods. The efficacy of benzimidazole drugs against early development stages of gastrointestinal nematodes was evaluated on 58 male calves aged 12–18 months spontaneously infected with gastrointestinal strongylates on the Moscow Region farms contaminated by nematode parasites. The animals were weighed, numbered and divided into experimental and control groups of 7–10 animals each. The male calves from different experimental groups were orally administered Panacur, Febtal, Fenbendazole (substance), Alben, Alvet, Valbazen, Closalben and Albendazole 10% powder once at a dose of 7.5 mg/kg for the active substance. The control animals did not receive the drug. The drug efficacy was recorded in the experiments of the "control test" type based on the coproovoscopic examination results by the flotation method using a VIGIS counting chamber, and on the results of helminthological dissections of the digestive tract of 3–5 animals from each group. The drug efficacy was recorded as per the Guidelines Approved by the World Association for the Advancement of Veterinary Parasitology (1995). The results were processed statistically using the Microsoft Excel computer tool.Results and discussion. We established the 94.4–97.2% efficacy of the drugs based on benzimidazoles, namely, Panacur, Febtal, Alben, Alvet, Valbazen and Closalben in therapeutic doses against imaginal gastrointestinal strongylates and 44.2–69.2% activity against nematode larvae.